2003
DOI: 10.1034/j.1600-0501.2003.00872.x
|View full text |Cite
|
Sign up to set email alerts
|

Osseointegration of endosseous ceramic implants after postoperative low‐power laser stimulation: an in vivo comparative study

Abstract: Stimulation with low-power laser (LPL) can enhance bone repair as reported in experimental studies on bone defects and fracture healing. Little data exist concerning the use of LPL postoperative stimulation to improve osseointegration of endosseous implants in orthopaedic and dental surgery. An in vivo model was used for the present study to evaluate whether Ga-Al-As (780 nm) LPL stimulation can improve biomaterial osseointegration. After drilling holes, cylindrical implants of hydroxyapatite (HA) were placed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
1
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 37 publications
3
24
1
8
Order By: Relevance
“…Kadra et al (2004) agree that no standard protocol for laser irradiation has yet been defined with reference to implant dentistry. It has been observed that there is a very large variation in the choice of energy density and wavelengths for the use of low-level laser irradiation in bone tissue [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kadra et al (2004) agree that no standard protocol for laser irradiation has yet been defined with reference to implant dentistry. It has been observed that there is a very large variation in the choice of energy density and wavelengths for the use of low-level laser irradiation in bone tissue [14].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that lasers have demonstrated efficiency on osseous tissue healing [4,[10][11][12][13][14], in implantology, factors like high initial stability, implant geometry, and good bone quality, are more relevant for the quality of the implantbone interface than any additional therapeutic effort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aplicaciones del láser de baja pótencia en Odontología RCOE, 2004, Vol 9, Nº5, 517-524 17 en el que se irradiaron las zonas periimplantarias en el fémur de conejos, observando mayor viabilidad ósea en la interfase entre el hueso y los implantes. Sin embargo, es necesario la realización de otros estudios clínicos que apoyen estas conclusiones.…”
Section: Implantología Bucofacialunclassified
“…Scientiic evidence demonstrates increased mechanical strength of the bone-implant connection, [4][5][6][7][8][9] enhanced metabolic activity of bone cells 10 and expansion of angiogenesis activity at sites treated with LLLT. 11 he biostimulation repair triggered by laser radiation is subject to a combination of parameters that comprise application protocols.…”
Section: Introductionmentioning
confidence: 99%